Pengaruh Ukuran Perusahaan, Ukuran Kantor Akuntan Publik dan Financial Distress Terhadap Opini Audit Going Concern (Studi Empiris pada Perusahaan Sub-Sektor Makanan dan Minuman Tahun 2019-2022) - Allaamsyah, Sayyid; ., Indupurnahayu; Riani, Desmy (CV. ITTC INDONESIA, 2025)
In 2019, food and beverage sub-sector companies recorded significant economic growth of 7.72%. However, in 2020, there was a decline in growth in most companies in the sub-sector. This condition indicates that food and beverage sub-sector companies experienced fluctuating growth, namely positive growth in 2019 and a decline in 2020. Companies that are experiencing going concern or non-going concern are based on various factors, such as the size of the company, the size of the public accounting firm and financial distress. This study aims to determine the effect of company size, the size of the public accounting firm and financial distress on going concern audit opinions (an empirical study of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2019-2022). The population in this study were food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2019-2022, consisting of 49 companies with an observation period of 4 years. This research method is quantitative and the method used for sampling in this study is purposive sampling. Based on the research results, the variables of company size and the size of the public accounting firm do not affect the going concern audit opinion. Then the financial distress variable has a positive effect on the going concern audit opinion.